Novoveška estetika in mistika - Jovanovski, Alenka (Primerjalna književnost, 2002)
Modern aesthetics and mysticism. The paper explores the experience of the beautiful as possibly a common ground between mysticism and modern aesthetics. The evolution of the latter - considered in the light of Gadamer's thesis on the subjectification of aesthetics since Kant - is thus set against the background of Platonic philosophy and the mystical aesthetics of Pseudo-Dionysius the Areopagite. On the other hand, it is interested in the aesthetics between Kant and Iser whose theory does not agree with Kant's thesis about the lack of cognitive value in the aesthetic experience. Despite the striking analogy with the mystical ascent to God, the aesthetic experience remains limited in the subject-object relationship, and that is why also the act of reading ends only in the reader's cognition of himself.
Keywords: aesthetics; estetika; mistika; literarna recepcija; spoznavna teorija; novi vek